Factors influencing adoption of building information modeling by Malaysian quantity surveying firms - Julian Osman (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Building Information Modeling (BIM) is making its way into more professional firms/ organisations within the architecture, engineering and construction (AEC) industry. However, quantity surveying (QS) firms/ organisations have been singled out to be slow adopters. Despite its reported benefits, the uptake by QS firms/ organisations has still been found to be considerably low. Review of the extant literature on BIM adoption has shown that limited studies were undertaken to determine the factors that influence organizational adoption of BIM, with specific reference to QS firms/ organisations. Thus, the aim of this study was to determine the significant factors that influence the intention to adopt BIM by Malaysian QS firms/ organisations. Two main research objectives were formulated which are i) To ascertain the level of awareness and understanding of BIM concepts among QSs, and ii) To determine factors within the context of Technology, Organisation and Environment and their influence on the adoption of BIM by QS firms. By synthesising Diffusion of Innovation (DOI) theory, Institutional Theory and Technology-Organisation-Environment framework, a conceptual model was developed. The technology context was represented by four independent variables namely (i) relative advantage, (ii) complexity, (iii) interoperability and (iv) cost. Within the organisational context, five independent variables namely (i) top management support, (ii) technology readiness, (iii) financial resources, (iv) training and (v) perceived risks were identified. Moreover, under the environmental context, three independent variables namely were identified: (i) external pressure, (ii) external support and (iii) government support. All these contexts were then used to predict the intention to adopt BIM within QS firms/ organsations in Malaysia. This study utilized questionnaire survey as the primary data collection method which was sent to 315 registered Malaysian QS firms/ organisations. Apart from descriptive statistics, structural equation modelling was used as the data analysis method. The research findings indicated the validity of a second-order factor of all the hypothesized contexts. Technology contexts has been found to be a second-order factor with four dimensions namely relative advantage, complexity, interoperability and cost. In addition, the organisational context has also been found to be a second-order factor with five dimensions namely top management support, technology readiness, financial resources, training and perceived risks. Lastly, the environmental context has also been found to be a second-order factor with three dimensions namely external pressure, external support and government support. Furthermore, this study has also asserted that the technological context to be the most influential context on the intention to adopt BIM by Malaysian QS firms. This is followed by the organizational context. However, the environmental context has been found to have no significant influence on the intention to adopt BIM by Malaysian QS firms. Thus, this study suggests that management of QS firms allocate sufficient resources to tackle the technology context and organistional context in order to increase the chances of adopting BIM.